2013
DOI: 10.1016/j.bbi.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Total and differential white blood cell counts, high-sensitivity C-reactive protein, and the metabolic syndrome in non-affective psychoses

Abstract: The metabolic syndrome is highly prevalent in patients with schizophrenia, and is associated with a state of chronic, low-grade inflammation. Schizophrenia is also associated with increased inflammation, including aberrant blood levels of pro-inflammatory cytokines and high-sensitivity C-reactive protein (hsCRP). The purpose of this study is to investigate the relationship between total and differential white blood cell (WBC) counts, hsCRP, and the metabolic syndrome in patients with schizophrenia and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 33 publications
1
43
1
Order By: Relevance
“…These results are consistent with a previous cross-sectional study, which identified hsCRP as a predictor of elevated triglyceride levels in a non-affective psychoses sample (Miller et al, 2013); our findings suggest that this association also holds for longitudinal changes, and applies also to patients with a range of psychosis diagnostic categories. Interestingly, in our sample changes in hsCRP were found to predict increases in triglycerides independent of changes in weight, which to date has been considered as the main risk factor for metabolic changes in FEP.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with a previous cross-sectional study, which identified hsCRP as a predictor of elevated triglyceride levels in a non-affective psychoses sample (Miller et al, 2013); our findings suggest that this association also holds for longitudinal changes, and applies also to patients with a range of psychosis diagnostic categories. Interestingly, in our sample changes in hsCRP were found to predict increases in triglycerides independent of changes in weight, which to date has been considered as the main risk factor for metabolic changes in FEP.…”
Section: Discussionsupporting
confidence: 94%
“…One previous longitudinal study found that elevated baseline Interleukin (IL)-1b levels predicted an increased risk of weight gain in patients six-months after the initiation of risperidone treatment (Song et al, 2014). Also of note, in a recent cross-sectional study in patients with psychosis, hsCRP predicted metabolic syndrome, as well as, independently, increased waist circumference and elevated triglycerides (Miller et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Dyslipidaemia has been shown to be associated with first-episode psychosis (Perry et al, 2016, Misiak et al, 2017b, and an abnormal inflammatory response in patients with first-episode psychosis (Russell et al, 2015, Miller et al, 2013. It is therefore possible that our hypothesis may extend to other elements of the metabolic syndrome, and this may warrant future research.…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…Interestingly, there is evidence in the literature that abnormal inflammatory markers are also associated with dyslipidaemia in studies of patients with first-episode psychosis (Russell et al, 2015, Miller et al, 2013, suggesting our hypothesis may be significant not only for dysglycaemia in first-episode psychosis, but dyslipidaemia also.…”
mentioning
confidence: 98%